Composition, cured product, sealing material for organic electroluminescence display element, and organic electroluminescence display device

JP7638220B2Active Publication Date: 2025-03-03DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021558398
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-18
Filing Date
2020-11-17
Publication Date
2025-03-03
Estimated Expiration
2040-11-17

AI Technical Summary

Benefits of technology

【0022】 本発明によれば、面内平坦性及び端部平坦性に優れた有機膜を形成可能な組成物が提供される。また、本発明によれば、上記組成物の硬化体であり、有機EL表示素子用封止材として有用な硬化体が提供される。更に、本発明によれば、上記硬化体を含む有機EL表示素子用封止材、及び、当該封止材を含む有機EL表示装置が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638220000001
    Figure 0007638220000001
  • Figure 0007638220000002
    Figure 0007638220000002
  • Figure 0007638220000003
    Figure 0007638220000003
Patent Text Reader

Abstract

A composition comprising a monomer ingredient and a photoplymerization initiator, wherein 97 mass% or more of the monomer ingredient is a monomer satisfying relationships (i) and (ii), at least some of the monomer ingredient is a fluoromonomer satisfying relationship (iii) and having both a fluorine atom and an unsaturated carbon-carbon double bond, and at least some of the monomer ingredient is a high-viscosity monomer satisfying relationship (vi). (i): │γC-γA│<20 mN / m (ii): │ƞA-ƞC│<3,000 mPa·s (iii): 1 mPa·s≤│ƞA1-ƞC│≤30 mPa·s (iv): 50 mPa·s≤│ƞA2-ƞC│≤3,000 mPa·s
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition and a cured product thereof. The present invention also relates to a sealing material for an organic electroluminescence (EL) display element and an organic EL display device including the same. [Background technology]

[0002] Organic electroluminescence display elements (also called organic EL display elements, organic EL elements, or OLED elements) have been attracting attention as elements capable of emitting light with high brightness. However, organic EL display elements have a problem in that they are deteriorated by moisture, resulting in a decrease in their light-emitting characteristics.

[0003] In order to solve such problems, techniques have been investigated for sealing an organic EL display element with a sealing material in which an organic film and an inorganic film are laminated, thereby preventing deterioration due to moisture (eg, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-307873 A [Patent Document 2] JP 2009-37812 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, the required characteristics of organic EL display elements have increased, and there is a demand for encapsulating materials that can achieve higher reliability and durability.

[0006] As a method for forming an encapsulant, a method is known in which an organic film is formed by coating and curing a resin composition, and an inorganic film is laminated on the organic film. This method has a problem that unevenness occurs on the surface of the coating film of the resin composition, and the unevenness of the surface of the organic film formed reduces adhesion to the inorganic film.

[0007] The unevenness of an organic film includes unevenness occurring within the surface of the organic film and protrusions caused by swelling at the edges of the organic film, and it is desirable to flatten both of these.

[0008] Therefore, an object of the present invention is to provide a composition capable of forming an organic film having excellent in-plane flatness (hereinafter sometimes referred to as surface flatness) and edge flatness. Another object of the present invention is to provide a cured product of the above composition, which is useful as a sealant for organic EL display elements. Still another object of the present invention is to provide a sealant for organic EL display elements comprising the above cured product, and an organic EL display device comprising the sealant. [Means for solving the problem]

[0009] One aspect of the present invention relates to a composition comprising a monomer component and a photopolymerization initiator. In the composition, 97% by mass or more of the monomer component is a monomer that satisfies the following formulas (i) and (ii). At least a part of the monomer component is a fluorine-containing monomer that satisfies the following formula (iii) and has a fluorine atom and a carbon-carbon unsaturated double bond. At least a part of the monomer component is a high-viscosity monomer that satisfies the following formula (vi). |γ C -γ A |<20mN / m …(i) [In the formula, γ C represents the surface tension (mN / m) of the composition, and γ A indicates the surface tension of the monomer (mN / m). |η A -η C |<3000mPa·s …(ii) [In the formula, η C indicates the viscosity (mPa s) of the above composition at 25°C, and η A indicates the viscosity (mPa·s) of the monomer at 25°C.] 1mPa·s≦|η A1 -η C |≦30 mPa·s …(iii) [In the formula, η Cindicates the viscosity (mPa s) of the above composition at 25°C, and η A1 indicates the viscosity (mPa s) of the above fluoromonomer at 25°C.] 50mPa·s≦|η A2 -η C |<3000mPa·s …(iv) [In the formula, η C indicates the viscosity (mPa s) of the above composition at 25°C, and η A2 indicates the viscosity (mPa·s) of the high-viscosity monomer at 25°C.

[0010] In one embodiment, the fluorine-containing monomer may satisfy the following formula (iii-a): 5mPa·s≦|η A1 -η C |≦20mPa·s …(iii-a)

[0011] In one embodiment, the high viscosity monomer may satisfy the following formula (iv-a): 70mPa·s≦|η A2 -η C |≦1000mPa·s …(iv-a)

[0012] In the composition according to one embodiment, the high viscosity monomer may account for 5 to 65% by mass of the monomer component.

[0013] In one embodiment, at least a portion of the monomer components may be a polyfunctional monomer having two or more carbon-carbon unsaturated double bonds.

[0014] In the composition according to one embodiment, the polyfunctional monomer may account for 70 to 98% by mass of the monomer component.

[0015] In one embodiment, the surface tension γ of the composition C may be 10 mN / m or more and 50 mN / m or less.

[0016] In one embodiment, the viscosity η of the composition at 25°C Cmay be 3 mPa·s or more and 50 mPa·s or less.

[0017] The composition can be suitably used as a sealant for an organic electroluminescence display device.

[0018] Another aspect of the present invention relates to a cured product obtained by curing the above composition.

[0019] Yet another aspect of the present invention relates to a sealing material for an organic electroluminescence display device, comprising the above-mentioned cured product.

[0020] Yet another aspect of the present invention relates to a sealing material for an organic electroluminescence display element, comprising a laminate in which an inorganic film and an organic film are laminated, the organic film comprising the cured product.

[0021] Yet another aspect of the present invention relates to an organic electroluminescent display device including an organic electroluminescent display element and the above-mentioned sealing material for an organic electroluminescent display element. Effect of the Invention

[0022] According to the present invention, there is provided a composition capable of forming an organic film having excellent in-plane flatness and edge flatness. According to the present invention, there is also provided a cured product of the composition, which is useful as a sealant for an organic EL display element. According to the present invention, there is further provided a sealant for an organic EL display element comprising the cured product, and an organic EL display device comprising the sealant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Preferred embodiments of the present invention will now be described in detail.

[0024] <Composition> The composition of the present embodiment includes a monomer component and a photopolymerization initiator. In the present embodiment, 97% by mass or more of the monomer component is a monomer that satisfies both of the following formulas (i) and (ii): γ Ais the surface tension of each monomer component used. η A is the viscosity of each monomer component used. η A1 is the viscosity of each monomer component used. η A2 is the viscosity of each monomer component used. |γ C -γ A |<20mN / m …(i) [In the formula, γ C represents the surface tension (mN / m) of the composition of this embodiment, and γ A indicates the surface tension of the monomer (mN / m). |η A -η C |<3000mPa·s …(ii) [In the formula, η C indicates the viscosity (mPa s) of the composition of this embodiment at 25°C, and η A indicates the viscosity (mPa·s) of the monomer at 25°C.]

[0025] In the present embodiment, at least a part of the monomer components is a fluorine-containing monomer that satisfies the following formula (iii) and has a fluorine atom and a carbon-carbon unsaturated double bond. 1mPa·s≦|η A1 -η C |≦30 mPa·s …(iii) [In the formula, η C indicates the viscosity (mPa s) of the composition of this embodiment at 25°C, and η A1 indicates the viscosity (mPa s) of the fluorine-containing monomer at 25°C.]

[0026] Furthermore, in this embodiment, at least a portion of the monomer component is a high-viscosity monomer that satisfies the following formula (vi). 50mPa·s≦|η A2 -η C |<3000mPa·s …(iv) [In the formula, η C indicates the viscosity (mPa s) of the composition of this embodiment at 25°C, and η A2 indicates the viscosity (mPa·s) of the high-viscosity monomer at 25°C.]

[0027] The composition of the present embodiment combines a specific fluorine-containing monomer with a specific high-viscosity monomer, and limits the surface tension and viscosity of the entire monomer components within a specific range, so that the coating surface of the composition is easily flattened and the swelling of the edges is suppressed. Therefore, the composition of the present embodiment can form an organic film with excellent in-plane flatness and edge flatness.

[0028] The reason why the above-mentioned effect is exhibited is not necessarily limited, but is considered to be as follows. First, since the composition of the present embodiment contains a fluorine-containing monomer, it is considered that the surface free energy is low, the coating film surface is easily flattened after application, and an organic film with less surface irregularities can be formed. In addition, the composition of the present embodiment is considered to suppress the volume reduction during curing of the coating film and the associated migration of the coating liquid to the edge by blending a high-viscosity monomer while keeping the surface tension and viscosity of the entire monomer components within a predetermined range, thereby improving the edge flatness.

[0029] At least a part of the monomer components of the present embodiment is a high-viscosity monomer having a viscosity of 50 mPa·s or more measured by an E-type viscometer at 25°C. The viscosity of the high-viscosity monomer is preferably 100 mPa·s or more, more preferably 150 mPa·s or more. The viscosity of the high-viscosity monomer is preferably 1000 mPa·s or less, more preferably 500 mPa·s or less, and even more preferably 300 mPa·s or less. That is, the viscosity of the high-viscosity monomer may be, for example, 50 to 1000 mPa·s, 50 to 500 mPa·s, 50 to 300 mPa·s, 100 to 1000 mPa·s, 100 to 500 mPa·s, 100 to 300 mPa·s, 150 to 1000 mPa·s, 150 to 500 mPa·s, or 150 to 300 mPa·s, as measured by an E-type viscometer at 25°C.

[0030] The surface tension γ of the composition of this embodiment Cmay be, for example, 10 mN / m or more, preferably 20 mN / m or more, more preferably 23 mN / m or more, and even more preferably 24 mN / m or more. By having such a surface tension, the in-plane flatness of the coating film tends to be further improved. In addition, the surface tension γ of the composition of the present embodiment C may be, for example, 50 mN / m or less, preferably 35 mN / m or less, more preferably 33 mN / m or less, and even more preferably 32 mN / m or less. By having such a surface tension, the coating liquid can easily spread into a coating film, which is more suitable for coating methods such as the inkjet method. That is, the surface tension γ of the composition of this embodiment is C may be, for example, 10 to 50 mN / m, 10 to 35 mN / m, 10 to 33 mN / m, 10 to 32 mN / m or less, 20 to 50 mN / m, 20 to 35 mN / m, 20 to 33 mN / m, 20 to 32 mN / m or less, 23 to 50 mN / m, 23 to 35 mN / m, 23 to 33 mN / m, 23 to 32 mN / m or less, 24 to 50 mN / m, 24 to 35 mN / m, 24 to 33 mN / m, or 24 to 32 mN / m. In this specification, the surface tension is a value measured by a pendant drop method at 23°C.

[0031] Viscosity η of the composition of this embodiment C The viscosity η of the composition of the present embodiment may be, for example, 3 mPa·s or more, preferably 5 mPa·s or more, and more preferably 10 mPa·s or more. C may be, for example, 50 mPa·s or less, preferably 45 mPa·s or less, and more preferably 40 mPa·s or less. Such a viscosity makes it suitable for use in coating methods such as the inkjet method. That is, the viscosity η of the composition of this embodiment C may be, for example, 3 to 50 mPa·s, 3 to 45 mPa·s, 3 to 40 mPa·s, 5 to 50 mPa·s, 5 to 45 mPa·s, 5 to 40 mPa·s, 10 to 50 mPa·s, 10 to 45 mPa·s, or 10 to 40 mPa·s. In this specification, the viscosity indicates a value measured at 25°C using an E-type viscometer.

[0032] The composition of the present embodiment may contain, as monomer components, a high-viscosity monomer and a low-viscosity monomer (a monomer having a viscosity of less than 50 mPa s measured with an E-type viscometer at 25° C.) The ratio of the high-viscosity monomer to the low-viscosity monomer can be appropriately changed as long as the viscosity of the composition falls within the above-mentioned numerical range.

[0033] The proportion of the high-viscosity monomer in the monomer components may be, for example, 5% by mass or more, preferably 7% by mass or more, and more preferably 9% by mass or more. By increasing the proportion of the high-viscosity monomer, the edge flatness tends to be improved. In addition, the proportion of the high-viscosity monomer in the monomer components may be, for example, 65% by mass or less, preferably 60% by mass or less, more preferably 55% by mass or less, 50% by mass or less, 40% by mass or less, or 35% by mass or less. By decreasing the proportion of the high-viscosity monomer, the viscosity of the composition can be reduced, and the in-plane flatness tends to be improved. That is, the proportion of the high-viscosity monomer in the monomer components may be, for example, 5 to 65 mass%, 5 to 60 mass%, 5 to 55 mass%, 5 to 50 mass%, 5 to 40 mass%, 5 to 35 mass%, 7 to 65 mass%, 7 to 60 mass%, 7 to 55 mass%, 7 to 50 mass%, 7 to 40 mass%, 7 to 35 mass%, 9 to 65 mass%, 9 to 60 mass%, 9 to 55 mass%, 9 to 50 mass%, 9 to 40 mass%, or 9 to 35 mass%.

[0034] Viscosity η of high viscosity monomer A2 and the viscosity η of the composition C Difference from |η A2 -η C is 50 mPa·s or more, preferably 70 mPa·s or more, more preferably 90 mPa·s or more, and even more preferably 100 mPa·s or more. A2 and the viscosity η of the composition C Difference from |η A2 -η Cis less than 3000 mPa·s, preferably 1000 mPa·s or less, more preferably 800 mPa·s or less, and even more preferably 600 mPa·s or less. That is, the difference |η A2 -η C may be, for example, 50 mPa·s or more and less than 3000 mPa·s, 50 to 1000 mPa·s, 50 to 800 mPa·s, 50 to 600 mPa·s, 70 mPa·s or more and less than 3000 mPa·s, 70 to 1000 mPa·s, 70 to 800 mPa·s, 70 to 600 mPa·s, 90 mPa·s or more and less than 3000 mPa·s, 90 to 1000 mPa·s, 90 to 800 mPa·s, 90 to 600 mPa·s, 100 mPa·s or more and less than 3000 mPa·s, 100 to 1000 mPa·s, 100 to 800 mPa·s, or 100 to 600 mPa·s.

[0035] The composition of the present embodiment may contain, as monomer components, a monofunctional monomer having one carbon-carbon unsaturated double bond and a polyfunctional monomer having two or more carbon-carbon unsaturated double bonds.

[0036] The ratio of the polyfunctional monomer in the monomer components may be, for example, 10% by mass or more, preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more. By increasing the ratio of the polyfunctional monomer, the moisture permeability of the cured body tends to be lower. In addition, the ratio of the polyfunctional monomer in the monomer components may be, for example, 98% by mass or less, preferably 97% by mass or less, and more preferably 96% by mass or less. By decreasing the ratio of the polyfunctional monomer, the flexibility of the cured body tends to be improved. That is, the ratio of the polyfunctional monomer in the monomer components may be, for example, 10 to 98% by mass, 10 to 97% by mass, 10 to 96% by mass, 70 to 98% by mass, 70 to 97% by mass, 70 to 96% by mass, 75 to 98% by mass, 75 to 97% by mass, 75 to 96% by mass, 80 to 98% by mass, 80 to 97% by mass, or 80 to 96% by mass.

[0037] As the polyfunctional monomer, a monomer having 2 to 6 carbon-carbon unsaturated double bonds is preferable, a monomer having 2 or 3 carbon-carbon unsaturated double bonds is more preferable, and a bifunctional monomer having 2 carbon-carbon unsaturated double bonds is even more preferable.

[0038] The composition of the present embodiment may contain a polyfunctional monomer as a high-viscosity monomer, may contain a polyfunctional monomer as a low-viscosity monomer, or may contain both a polyfunctional monomer corresponding to a high-viscosity monomer and a polyfunctional monomer corresponding to a low-viscosity monomer.

[0039] The composition of the present embodiment may contain a monofunctional monomer as the high-viscosity monomer, may contain a monofunctional monomer as the low-viscosity monomer, or may contain both a monofunctional monomer corresponding to a high-viscosity monomer and a monofunctional monomer corresponding to a low-viscosity monomer.

[0040] In this embodiment, it is preferable that at least a part of the high-viscosity monomer is a monofunctional monomer.

[0041] The ratio of the monofunctional monomer in the high-viscosity monomer may be, for example, 9% by mass or more, preferably 10% by mass or more, more preferably 11% by mass or more, and even more preferably 12% by mass or more. The ratio of the monofunctional monomer in the high-viscosity monomer may be, for example, 60% by mass or less, preferably 55% by mass or less, and more preferably 50% by mass or less. By using a large amount of monofunctional monomer as the high-viscosity monomer, the moisture permeability, flexibility, and flexibility of the cured body tend to be further improved. That is, the ratio of the monofunctional monomer in the high-viscosity monomer may be, for example, 9 to 60% by mass, 9 to 55% by mass, 9 to 50% by mass, 10 to 60% by mass, 10 to 55% by mass, 10 to 50% by mass, 11 to 60% by mass, 11 to 55% by mass, 11 to 50% by mass, 12 to 60% by mass, 12 to 55% by mass, or 12 to 50% by mass.

[0042] <Fluorine-containing monomer> The fluorine-containing monomer is a monomer having a fluorine atom and a carbon-carbon unsaturated double bond. The fluorine-containing monomer may be used alone or in combination of two or more kinds.

[0043] The fluorine-containing monomer may be included in the monomer component as a low-viscosity monomer. A1 The viscosity η of the fluorine-containing monomer (measured by an E-type viscometer at 25° C.) may be, for example, less than 50 mPa·s, and is preferably 45 mPa·s or less, more preferably 40 mPa·s or less, and further preferably 35 mPa·s or less. A1 (viscosity measured by an E-type viscometer at 25° C.) may be, for example, 1 mPa·s or more, 2 mPa·s or more, or 3 mPa·s or more. That is, the viscosity η of the fluorine-containing monomer A1 The viscosity, as measured at 25°C using an E-type viscometer, may be, for example, 1 mPa·s or more and less than 50 mPa·s, 1 to 45 mPa·s, 1 to 40 mPa·s, 1 to 35 mPa·s, 2 mPa·s or more and less than 50 mPa·s, 2 to 45 mPa·s, 2 to 40 mPa·s, 2 to 35 mPa·s, 3 mPa·s or more and less than 50 mPa·s, 3 to 45 mPa·s, 3 to 40 mPa·s, or 3 to 35 mPa·s.

[0044] Viscosity η of fluorine-containing monomer A1 and the viscosity η of the composition C Difference from |η A1 -η C is 1 mPa·s or more, and preferably 5 mPa·s or more. In addition, the viscosity η A1 and the viscosity η of the composition C Difference from |η A1 -η C is 30 mPa·s or less, and preferably 20 mPa·s or less. That is, the viscosity η of the fluorine-containing monomer A1 and the viscosity η of the composition C Difference from |η A1 -η Cmay be, for example, 1 to 30 mPa·s, 1 to 20 mPa·s, 5 to 30 mPa·s, or 5 to 20 mPa·s.

[0045] The number of fluorine atoms contained in the fluorine-containing monomer may be 1 or more, for example, 2 or more, and preferably 3 or more. The upper limit of the number of fluorine atoms contained in the fluorine-containing monomer is not particularly limited. The number of fluorine atoms contained in the fluorine-containing monomer may be, for example, 40 or less, preferably 35 or less, more preferably 30 or less, and further preferably 25 or less. That is, the number of fluorine atoms contained in the fluorine-containing monomer may be, for example, 1 to 40, 1 to 35, 1 to 30, 1 to 25, 2 to 40, 2 to 35, 2 to 30, 2 to 25, 3 to 40, 3 to 35, 3 to 30, or 3 to 25.

[0046] The content of fluorine atoms relative to the total amount of the fluorine-containing monomer may be, for example, 1% by mass or more, preferably 2% by mass or more, more preferably 5% by mass or more. The content of fluorine atoms may be, for example, 90% by mass or less, preferably 75% by mass or less, more preferably 70% by mass or less, and even more preferably 65% ​​by mass or less, based on the total amount of the fluorine-containing monomer. That is, the content of fluorine atoms may be 1 to 90% by mass, 1 to 75% by mass, 1 to 70% by mass, 1 to 65% by mass, 2 to 90% by mass, 2 to 75% by mass, 2 to 70% by mass, 2 to 65% by mass, 5 to 90% by mass, 5 to 75% by mass, 5 to 70% by mass, or 5 to 65% by mass, based on the total amount of the fluorine-containing monomer.

[0047] The number of carbon-carbon unsaturated double bonds in the fluorine-containing monomer may be 1 or more. The number of carbon-carbon unsaturated double bonds in the fluorine-containing monomer may be, for example, 4 or less, and from the viewpoint of easily obtaining a cured body having excellent flexibility, it is preferably 3 or less, more preferably 2 or less. That is, the number of carbon-carbon unsaturated double bonds in the fluorine-containing monomer may be, for example, 1 to 4, 1 to 3, or 1 to 2.

[0048] The fluorine-containing monomer preferably has a (meth)acryloyl group as a group having a carbon-carbon double bond. That is, the fluorine-containing monomer is preferably a monomer having a fluorine atom and a (meth)acryloyl group. Here, the (meth)acryloyl group refers to an acryloyl group or a methacryloyl group.

[0049] A specific example of the fluorine-containing monomer is a compound represented by the following formula (A-1).

[0050] [ka]

[0051] In formula (A-1), R 1 represents a hydrogen atom or a methyl group. 2 represents a fluorinated alkyl group or a group in which an oxygen atom has been inserted into part of the carbon-carbon bond and carbon-hydrogen bond in a fluorinated alkyl group.

[0052] The fluorinated alkyl group can be said to be a group in which some or all of the hydrogen atoms of an alkyl group are substituted with fluorine atoms. The number of carbon atoms of the fluorinated alkyl group is not particularly limited, and may be, for example, 1 or more, preferably 2 or more, and more preferably 3 or more. The number of carbon atoms of the fluorinated alkyl group may be, for example, 25 or less, or 20 or less. That is, the number of carbon atoms of the fluorinated alkyl group may be, for example, 1 to 25, 1 to 20, 2 to 25, 2 to 20, 3 to 25, or 3 to 20.

[0053] As the fluorinated alkyl group, a group containing difluoromethylene (-CF2-) can be suitably used.

[0054] Specific examples of fluorinated alkyl groups include a difluoromethyl group, a trifluoromethyl group, a 1,1-difluoroethyl group, a 2,2-difluoroethyl group, a 1,1,1-trifluoroethyl group, a 2,2,2-trifluoroethyl group, a perfluoroethyl group, a 1,1,2,2-tetrafluoropropyl group, a 1,1,1,2,2-pentafluoropropyl group, a 1,1,2,2,3,3-hexafluoropropyl group, a perfluoropropyl group, a perfluoroethylmethyl group, a 1-(trifluoromethyl)-1,2,2,2-tetrafluoroethyl group, a 2,2,3,3-tetrafluoropropyl group, a perfluoropropyl group, a 1,1,2,2-tetrafluorobutyl group, a 1,1,2,2,3,3-hexafluorobutyl group, a 1,1,1,2,2,3,3-peptafluorobutyl group, and a 1,1,2,2,3,3,4,4-octafluorobutyl group. Perfluorobutyl group, 1,1-bis(trifluoro)methyl-2,2,2-trifluoroethyl group, 2-(perfluoropropyl)ethyl group, 1,1,2,2,3,3,4,4-octafluoropentyl group, 2,2,3,3,4,4,5,5-octafluoropentyl group, perfluoropentyl group, 1,1,2,2,3,3,4,4,5,5-decafluoropentyl group, 1,1-bis(trifluoromethyl)-2 , 2,3,3,3-pentafluoropropyl group, 2-(perfluorobutyl)ethyl group, 1,1,1,2,2,3,3,4,4-nonafluoropentyl group, 1,1,2,2,3,3,4,4,5,5-decafluorohexyl group, 1,1,2,2,3,3,4,4,5,5,6,6-dodecafluorohexyl group, perfluorohexyl group, perfluoropentylmethyl group, and perfluorohexyl group.

[0055] A group in which an oxygen atom is inserted into a part of the carbon-carbon bond or carbon-hydrogen bond in a fluorinated alkyl group (hereinafter referred to as R 2 ) may be a group having an oxygen atom inserted at one position, or may be a group having an oxygen atom inserted at two or more positions.

[0056] When an oxygen atom is inserted into a carbon-carbon bond, an ether bond is formed. When an oxygen atom is inserted into a carbon-hydrogen bond, a hydroxyl group is formed. 2 The oxygen-containing group can also be said to be a group containing at least one type selected from the group consisting of an ether bond and a hydroxyl group.

[0057] R 2 Specific examples of the oxygen-containing group include groups represented by the following formulas.

[0058] [ka]

[0059] The fluorine atom content in the compound represented by formula (A-1) may be, for example, 2% by mass or more, preferably 5% by mass or more, more preferably 15% by mass or more, and even more preferably 30% by mass or more. The fluorine atom content in the compound represented by formula (A-1) may be, for example, 75% by mass or less, preferably 70% by mass or less, and more preferably 65% ​​by mass or less. That is, the fluorine atom content in the compound represented by formula (A-1) may be, for example, 2 to 75% by mass, 2 to 70% by mass, 2 to 65% by mass, 5 to 75% by mass, 5 to 70% by mass, 5 to 65% by mass, 15 to 75% by mass, 15 to 70% by mass, 15 to 65% by mass, 30 to 75% by mass, 30 to 70% by mass, or 30 to 65% by mass.

[0060] A specific example of the compound represented by formula (A-1) is a compound represented by formula (A-1-1).

[0061] [ka]

[0062] In formula (A-1-1), R 1 represents a hydrogen atom or a methyl group, R 21 represents a hydrogen atom or a fluorine atom, and n represents an integer of 1 or more.21 may be the same or different. However, R 21 At least one of the groups is a fluorine atom.

[0063] n may be 1 or more, and is preferably 2 or more. The upper limit of n is not particularly limited. n may be, for example, 25 or less, or 20 or less. That is, n may be, for example, 1 to 25, 1 to 20, 2 to 25, or 2 to 20.

[0064] R 21 is present in the formula (A-1-1), at least one of which is a fluorine atom. 21 Among these, preferably two or more are fluorine atoms, and more preferably three or more are fluorine atoms. 21 may all be fluorine atoms.

[0065] R 21 The ratio of the number of fluorine atoms to the total number of R may be, for example, 4% or more, preferably 8% or more, and more preferably 12% or more. The ratio may be, for example, 100% or less, preferably 80% or less, and more preferably 75% or less. That is, R 21 The ratio of the number of fluorine atoms to the total number may be, for example, 4 to 100%, 4 to 80%, 4 to 75%, 8 to 100%, 8 to 80%, 8 to 75%, 12 to 100%, 12 to 80%, or 12 to 75%.

[0066] The compound represented by formula (A-1-1) is a divalent group (-C(R 21 At least one of the groups represented by the formula (I)2-) is preferably difluoromethylene (-CF2-).

[0067] Another specific example of the fluorine-containing monomer is a compound represented by formula (A-2).

[0068] [ka]

[0069] In formula (A-2), R 3 represents a hydrogen atom or a methyl group. 4 represents a fluorinated alkanediyl group, or a group in which oxygen atoms have been inserted into some of the carbon-carbon bonds and carbon-hydrogen bonds in a fluorinated alkanediyl group. 3 may be the same or different from each other.

[0070] The fluorinated alkanediyl group can be said to be a group in which some or all of the hydrogen atoms of the alkanediyl group are substituted with fluorine atoms. The number of carbon atoms of the fluorinated alkanediyl group is not particularly limited, and may be, for example, 1 or more, preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more. The number of carbon atoms of the fluorinated alkanediyl group may be, for example, 20 or less, preferably 17 or less, more preferably 15 or less, even more preferably 12 or less, and even more preferably 10 or less. That is, the number of carbon atoms of the fluorinated alkanediyl group may be, for example, 1 to 20, 1 to 17, 1 to 15, 1 to 12, 1 to 10, 2 to 20, 2 to 17, 2 to 15, 2 to 12, 2 to 10, 3 to 20, 3 to 17, 3 to 15, 3 to 12, 3 to 10, 4 to 20, 4 to 17, 4 to 15, 4 to 12, or 4 to 10.

[0071] As the fluorinated alkanediyl group, a group containing difluoromethylene (-CF2-) can be suitably used.

[0072] Specific examples of the fluorinated alkanediyl group include linear or branched fluorinated alkanediyl groups having 1 to 17 carbon atoms (for example, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-hexadecafluoro-1,10-decanediyl group) and fluorinated cycloalkanediyl groups having 1 to 17 carbon atoms.

[0073] A group in which an oxygen atom is inserted into a part of the carbon-carbon bond and carbon-hydrogen bond in a fluorinated alkanediyl group (hereinafter referred to as R 4) may be a group having an oxygen atom inserted at one position, or may be a group having an oxygen atom inserted at two or more positions.

[0074] When an oxygen atom is inserted into a carbon-carbon bond, an ether bond is formed. When an oxygen atom is inserted into a carbon-hydrogen bond, a hydroxyl group is formed. 4 The oxygen-containing group can also be said to be a group containing at least one type selected from the group consisting of an ether bond and a hydroxyl group.

[0075] R 4 Specific examples of the oxygen-containing group include groups represented by the following formulas.

[0076] [ka]

[0077] The fluorine atom content in the compound represented by formula (A-2) may be, for example, 4% by mass or more, preferably 8% by mass or more, more preferably 12% by mass or more. The fluorine atom content in the compound represented by formula (A-2) may be, for example, 90% by mass or less, preferably 75% by mass or less, more preferably 65% ​​by mass or less. That is, the fluorine atom content in the compound represented by formula (A-2) may be, for example, 4 to 90% by mass, 4 to 75% by mass, 4 to 65% by mass, 8 to 90% by mass, 8 to 75% by mass, 8 to 65% by mass, 12 to 90% by mass, 12 to 75% by mass, or 12 to 65% by mass.

[0078] A specific example of the compound represented by formula (A-2) is a compound represented by formula (A-2-1).

[0079] [ka]

[0080] In formula (A-2-1), R 3 represents a hydrogen atom or a methyl group, R41 represents a hydrogen atom or a fluorine atom, and m represents an integer of 1 or more. 3 may be the same or different. 41 may be the same or different from each other. 41 At least one of the groups is a fluorine atom.

[0081] m may be 1 or more, preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more. The upper limit of m is not particularly limited. m may be, for example, 20 or less, preferably 17 or less, more preferably 15 or less, even more preferably 12 or less, and even more preferably 10 or less. That is, m may be, for example, 1 to 20, 1 to 17, 1 to 15, 1 to 12, 1 to 10, 2 to 20, 2 to 17, 2 to 15, 2 to 12, 2 to 10, 3 to 20, 3 to 17, 3 to 15, 3 to 12, 3 to 10, 4 to 20, 4 to 17, 4 to 15, 4 to 12, or 4 to 10.

[0082] R 41 There are a plurality of R in formula (A-2-1), and at least one of them is a fluorine atom. 41 Among these, preferably two or more are fluorine atoms, and more preferably four or more are fluorine atoms. 41 may all be fluorine atoms.

[0083] R 41 The ratio of the number of fluorine atoms to the total number of R may be, for example, 1% or more, preferably 5% or more, and more preferably 10% or more. The ratio may be, for example, 100% or less, preferably 95% or less, and more preferably 90% or less. That is, R 41 The ratio of the number of fluorine atoms to the total number may be, for example, 1 to 100%, 1 to 95%, 1 to 90%, 5 to 100%, 5 to 95%, 5 to 90%, 10 to 100%, 10 to 95%, or 10 to 90%.

[0084] The compound represented by formula (A-2-1) is a divalent group (-C(R 41At least one of the groups represented by the formula (I)2-) is preferably difluoromethylene (-CF2-).

[0085] Another specific example of the fluorine-containing monomer is a compound represented by formula (A-3).

[0086] [ka]

[0087] In formula (A-3), R 5 represents a hydrogen atom or a methyl group. 6 represents a single bond, an alkanediyl group, a fluorinated alkanediyl group, or a group in which oxygen atoms have been inserted into some of the carbon-carbon bonds and carbon-hydrogen bonds in an alkanediyl group or a fluorinated alkanediyl group. 1 represents a fluoroaryl group.

[0088] Furthermore, “R 6 "represents a single bond" means that Ar 1 This means that the oxygen atom is directly bonded to the

[0089] Ar 1 The fluorinated aryl group is preferably a fluorinated phenyl group. The fluorinated phenyl group can also be said to be a group in which 1 to 5 hydrogen atoms in a phenyl group are substituted with fluorine atoms. The fluorinated phenyl group may have one or more fluorine atoms, or may have five fluorine atoms.

[0090] R 6 The number of carbon atoms in the alkanediyl group is not particularly limited and may be, for example, 1 or more. 6 The number of carbon atoms in the alkanediyl group may be, for example, 17 or less, preferably 15 or less, and more preferably 12 or less. That is, R 6 The alkanediyl group may have, for example, 1 to 17, 1 to 15, or 1 to 12 carbon atoms.

[0091] Specific examples of the alkanediyl group include linear or branched alkanediyl groups having 1 to 17 carbon atoms (eg, methylene group, ethylene group, etc.) and cycloalkanediyl groups having 1 to 17 carbon atoms.

[0092] R 6 The fluorinated alkanediyl group of the formula R is a group in which some or all of the hydrogen atoms of the alkanediyl group have been substituted with fluorine atoms. 6 The number of carbon atoms in the fluorinated alkanediyl group is not particularly limited and may be, for example, 1 or more. 6 The number of carbon atoms in the fluorinated alkanediyl group may be, for example, 17 or less, preferably 15 or less, and more preferably 12 or less. That is, R 6 The fluorinated alkanediyl group may have, for example, 1 to 17, 1 to 15, or 1 to 12 carbon atoms.

[0093] R 6 As the fluorinated alkanediyl group, a group containing difluoromethylene (-CF2-) can be suitably used.

[0094] A group in which an oxygen atom has been inserted into a part of the carbon-carbon bond and carbon-hydrogen bond in an alkanediyl group or a fluorinated alkanediyl group (hereinafter referred to as R 6 ) may be a group having an oxygen atom inserted at one position, or may be a group having an oxygen atom inserted at two or more positions.

[0095] When an oxygen atom is inserted into a carbon-carbon bond, an ether bond is formed. When an oxygen atom is inserted into a carbon-hydrogen bond, a hydroxyl group is formed. 6 The oxygen-containing group can also be said to be a group containing at least one type selected from the group consisting of an ether bond and a hydroxyl group.

[0096] R 6 Specific examples of the oxygen-containing group include groups containing -CH2CH2O-.

[0097] The fluorine atom content in the compound represented by formula (A-3) may be, for example, 3% by mass or more, preferably 7% by mass or more, and more preferably 15% by mass or more. The fluorine atom content in the compound represented by formula (A-3) may be, for example, 90% by mass or less, preferably 80% by mass or less, and more preferably 70% by mass or less. That is, the fluorine atom content in the compound represented by formula (A-3) may be, for example, 3 to 90% by mass, 3 to 80% by mass, 3 to 70% by mass, 7 to 90% by mass, 7 to 80% by mass, 7 to 70% by mass, 15 to 90% by mass, 15 to 80% by mass, or 15 to 70% by mass.

[0098] A specific example of the compound represented by formula (A-3) is a compound represented by formula (A-3-1).

[0099] [ka]

[0100] In formula (A-3-1), R 5 represents a hydrogen atom or a methyl group, R 61 represents a hydrogen atom or a fluorine atom, R 62 represents a hydrogen atom or a fluorine atom, and p represents an integer of 0 or more. When p is 1 or more, a plurality of R 61 may be the same or different. 62 may be the same or different from each other. 62 At least one of the groups is a fluorine atom.

[0101] p represents an integer of 0 or more. Here, when p is 0, it means that the benzene ring and the oxygen atom are directly bonded. p may be an integer of 1 or more. In addition, the upper limit of p is not particularly limited. p may be, for example, 17 or less, preferably 15 or less, and more preferably 12 or less. That is, p may be, for example, 1 to 17, 1 to 15, or 1 to 12.

[0102] R in formula (A-3-1) 61exists (i.e., p is an integer equal to or greater than 1), then R 61 may all be hydrogen atoms, may all be fluorine atoms, or may be partly hydrogen atoms and the other part (hereinafter sometimes referred to as the other part) be fluorine atoms.

[0103] R 62 is present in the formula (A-3-2), and at least one of them is a fluorine atom. 62 Among these, two or more may be fluorine atoms, or three or more may be fluorine atoms. 62 All (five) of the above may be fluorine atoms.

[0104] R 61 and R 62 The ratio of the number of fluorine atoms to the total number of R may be, for example, 5% or more, preferably 10% or more, and more preferably 20% or more. The ratio may be, for example, 100% or less, preferably 95% or less, and more preferably 80% or less. That is, R 61 and R 62 The ratio of the number of fluorine atoms to the total number may be, for example, 5 to 100%, 5 to 95%, 5 to 80%, 10 to 100%, 10 to 95%, 10 to 80%, 20 to 100%, 20 to 95%, or 20 to 80%.

[0105] In a preferred embodiment, the fluorine-containing monomer preferably contains at least one selected from the group consisting of a compound represented by formula (A-1), a compound represented by formula (A-2), and a compound represented by formula (A-3).

[0106] In another preferred embodiment, the fluorine-containing monomer preferably includes at least one selected from the group consisting of 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl (meth)acrylate, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-hexadecafluoro-1,10-decanediol di(meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, and 1H,1H,2H,2H-tridecafluorooctyl (meth)acrylate.

[0107] The fluorine-containing monomer is not limited to the above compounds.

[0108] In this embodiment, the monomer component may further contain a monomer other than the fluorine-containing monomer (i.e., a monomer having no fluorine atoms) (hereinafter, also referred to as monomer (B)). Monomer (B) can be said to be a monomer having a carbon-carbon unsaturated double bond and having no fluorine atoms. Monomer (B) is preferably a monomer having a vinyl group as the carbon-carbon unsaturated double bond, and more preferably a monomer having a (meth)acryloyl group as the carbon-carbon unsaturated double bond.

[0109] The proportion of the fluorine-containing monomer in the monomer components is not particularly limited, and may be, for example, 0.001% by mass or more, preferably 0.005% by mass or more, and more preferably 0.008% by mass or more. The proportion of the fluorine-containing monomer in the monomer components may be, for example, 97% by mass or less, preferably 95% by mass or less, and more preferably 93% by mass or less. That is, the proportion of the fluorine-containing monomer in the monomer components may be, for example, 0.001 to 97% by mass, 0.001 to 95% by mass, 0.001 to 93% by mass, 0.005 to 97% by mass, 0.005 to 95% by mass, 0.005 to 93% by mass, 0.008 to 97% by mass, 0.008 to 95% by mass, or 0.008 to 93% by mass.

[0110] From the viewpoint of obtaining better in-plane flatness, the ratio of the fluorine-containing monomer in the monomer components is preferably 0.01% by mass or more, more preferably 0.1 to 10% by mass, even more preferably 0.3 to 7% by mass, and even more preferably 0.5 to 5% by mass. That is, the ratio of the fluorine-containing monomer in the monomer components may be, for example, 0.01 to 10% by mass, 0.01 to 7% by mass, 0.01 to 5% by mass, 0.1 to 10% by mass, 0.1 to 7% by mass, 0.1 to 5% by mass, 0.3 to 10% by mass, 0.3 to 7% by mass, 0.3 to 5% by mass, 0.5 to 10% by mass, 0.5 to 7% by mass, or 0.5 to 5% by mass.

[0111] The fluorine atom content relative to the total amount of the monomer components may be, for example, 0.005% by mass or more, preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, and even more preferably 5% by mass or more. The fluorine atom content may be, for example, 75% by mass or less, preferably 70% by mass or less, and more preferably 65% ​​by mass or less, based on the total amount of the monomer components. That is, the fluorine atom content relative to the total amount of the monomer components may be, for example, 0.005 to 75% by mass, 0.005 to 70% by mass, 0.005 to 65% by mass, 0.5 to 75% by mass, 0.5 to 70% by mass, 0.5 to 65% by mass, 1 to 75% by mass, 1 to 70% by mass, 1 to 65% by mass, 2 to 75% by mass, 2 to 70% by mass, 2 to 65% by mass, 5 to 75% by mass, 5 to 70% by mass, or 5 to 65% by mass.

[0112] The monomer (B) may be a high-viscosity monomer or a low-viscosity monomer, but it is preferable that at least a part of the monomer (B) is a high-viscosity monomer. The monomer component may contain two or more kinds of monomer (B), and in this case, all of the two or more kinds of monomer (B) may be high-viscosity monomers, or one part of the two or more kinds of monomer (B) may be a high-viscosity monomer and the other part may be a low-viscosity monomer.

[0113] Among the monomers (B), examples of the high viscosity monomers include 4-butylphenyl (meth)acrylate, phenyl (meth)acrylate, 2,4,5-tetramethylphenyl (meth)acrylate, 4-chlorophenyl (meth)acrylate, phenoxymethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate (2-HPA), 2-(meth)acryloyloxyhexahydrophthalic acid, ... aryloxyethyl-2-hydroxypropyl phthalate, EO modified phenol (meth)acrylate, EO modified cresol (meth)acrylate, EO modified nonylphenol (meth)acrylate, PO modified nonylphenol (meth)acrylate, ethoxylated-o-phenylphenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, propoxylated ethoxylated Bisphenol A di(meth)acrylate, bisphenol A epoxy di(meth)acrylate, ethoxylated-o-phenylphenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylol propane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and the like.

[0114] Among the monomers (B), examples of low viscosity monomers include 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate.

[0115] The monomer (B) may be a monofunctional monomer or a polyfunctional monomer, but it is preferable that at least a part of the monomer (B) is a monofunctional monomer, and it is more preferable that a part of the monomer (B) is a monofunctional monomer and the other part is a polyfunctional monomer. That is, the monomer component may contain two or more kinds of monomers (B), and it is preferable that a part of the two or more kinds of monomers (B) is a monofunctional monomer and the other part is a polyfunctional monomer.

[0116] Among the monomers (B), examples of the monofunctional monomers include 4-butylphenyl (meth)acrylate, phenyl (meth)acrylate, 2,4,5-tetramethylphenyl (meth)acrylate, 4-chlorophenyl (meth)acrylate, phenoxymethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate (2-HPA), 2-(meth)acryloyloxyhexahydrophthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalic acid, EO-modified phenol (meth)acrylate, EO-modified cresol (meth)acrylate, EO-modified nonylphenol (meth)acrylate, PO-modified nonylphenol (meth)acrylate, ethoxylated ... oxylated-o-phenylphenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and the like.

[0117] Among the monomers (B), examples of the polyfunctional monomers include ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, propoxylated ethoxylated bisphenol A di(meth)acrylate, bisphenol A epoxy di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, Examples of the acrylates include pentaerythritol tri(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and 1,12-dodecanediol di(meth)acrylate.

[0118] The photopolymerization initiator may be any compound that can be activated by active light such as visible light or ultraviolet light to initiate or promote polymerization of the monomer components. The photopolymerization initiator may be used alone or in combination of two or more. As the photopolymerization initiator, a photoradical polymerization initiator is preferred.

[0119] Examples of photoradical polymerization initiators include: Benzophenone and its derivatives; Benzil and its derivatives; Anthraquinone and its derivatives; Benzoin-type photopolymerization initiators such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isobutyl ether, and benzil dimethyl ketal; Acetophenone-type photopolymerization initiators such as diethoxyacetophenone and 4-tert-butyltrichloroacetophenone; 2-Dimethylaminoethyl benzoate; p-Dimethylaminoethyl benzoate; Diphenyl disulfide; Thioxanthone and its derivatives; camphorquinone-type photopolymerization initiators such as camphorquinone, 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxylic acid, 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxy-2-bromoethyl ester, 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxy-2-methyl ester, and 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxylic acid chloride; α-aminoalkylphenone type photopolymerization initiators such as 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1; acylphosphine oxide type photopolymerization initiators such as benzoyldiphenylphosphine oxide, diphenyl-2,4,6-trimethylbenzoylphosphine oxide, benzoyldiethoxyphosphine oxide, 2,4,6-trimethylbenzoyldimethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiethoxyphenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; Phenyl-glyoxylic acid-methyl ester; Oxy-phenyl-acetic acid 2-[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl ester; Oxy-phenyl-acetic acid 2-[2-hydroxy-ethoxy]-ethyl ester; and the like.

[0120] As the photopolymerization initiator, an acylphosphine oxide type photopolymerization initiator is preferred from the viewpoint of being able to cure using only visible light of 390 nm or more. The acylphosphine oxide type photopolymerization initiator can also be said to be a photopolymerization initiator having an acylphosphine oxide group (-(C=O)-(P=O)<). In addition, diphenyl-2,4,6-trimethylbenzoylphosphine oxide is particularly preferred from the viewpoint of being able to cure with light of 395 nm or more and being able to easily obtain a cured body with a higher visible light transmittance. As an example of diphenyl-2,4,6-trimethylbenzoylphosphine oxide, "Irgacure TPO" manufactured by BASF Japan Ltd. can be mentioned.

[0121] The content of the photopolymerization initiator is preferably 0.05 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 2 parts by mass or more, and even more preferably 2.5 parts by mass or more, relative to 100 parts by mass of the total amount of the monomer components. By increasing the content of the photopolymerization initiator, the curing performance of the composition tends to be further improved. The content of the photopolymerization initiator is preferably 12 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, relative to 100 parts by mass of the total amount of the monomer components. By reducing the content of the photopolymerization initiator, it becomes easier to obtain a cured product with a higher visible light transmittance. That is, the content of the photopolymerization initiator may be, for example, 0.05 to 12 parts by mass, 0.05 to 8 parts by mass, 0.05 to 6 parts by mass, 0.5 to 12 parts by mass, 0.5 to 8 parts by mass, 0.5 to 6 parts by mass, 2 to 12 parts by mass, 2 to 8 parts by mass, 2 to 6 parts by mass, 2.5 to 12 parts by mass, 2.5 to 8 parts by mass, or 2.5 to 6 parts by mass, relative to 100 parts by mass of the total amount of the monomer components.

[0122] The composition of the present embodiment may further contain other components than the monomer component and the photopolymerization initiator. The composition of the present embodiment may further contain, for example, known additives used in the field of sealants for organic EL display elements. Examples of additives include antioxidants, metal deactivators, fillers, stabilizers, neutralizers, lubricants, antibacterial agents, etc.

[0123] The composition of the present embodiment can be cured by irradiation with at least one of visible light and ultraviolet light. In this specification, the "curing" of the composition is not necessarily limited to rigid solidification, but may mean that the monomer components are polymerized to form a polymer. For example, the cured product of the composition may be a rigid solid (e.g., glassy) or rubbery.

[0124] Examples of energy irradiation sources for irradiating visible light or ultraviolet light include deuterium lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, low-pressure mercury lamps, xenon lamps, xenon-mercury hybrid lamps, halogen lamps, excimer lamps, indium lamps, thallium lamps, LED lamps, and electrodeless discharge lamps.

[0125] The composition of the present embodiment is preferably cured with light having a wavelength of 380 nm or more, more preferably with light having a wavelength of 395 nm or more, and most preferably with light having a wavelength of 395 nm, from the viewpoint of preventing damage to the organic EL display element. The wavelength of the irradiated light is preferably 500 nm or less, since this avoids the temperature rise of the irradiated part due to infrared light and reduces the possibility of damaging the organic EL display element. As the energy irradiation source, an LED lamp having a single wavelength of light emission is preferable.

[0126] The amount of radiation used to cure the composition is 100 to 8000 mJ / cm 2 is preferably 300 to 2000 mJ / cm 2 It is more preferable that the irradiation dose is 100 mJ / cm. 2 By setting the irradiation dose at 8000 mJ / cm or more, the composition is sufficiently cured and high adhesive strength is easily obtained. 2 By setting the amount of irradiation to the range below, the composition can be cured without damaging the organic EL display element. That is, the amount of irradiation when curing the composition is, for example, 100 to 8000 mJ / cm 2 2 , 300~8000mJ / cm 2 , 100~2000mJ / cm 2 , 300~2000mJ / cm2 It may be.

[0127] The cured product of the composition of the present embodiment is preferably excellent in transparency. Specifically, the cured product has a spectral transmittance of 95% or more, more preferably 97% or more, and even more preferably 99% or more per 10 μm thickness in the ultraviolet-visible region of 360 nm to 800 nm. If the spectral transmittance is 95% or more, an organic EL display device having excellent brightness and contrast can be easily obtained.

[0128] The cured product of the composition of the present embodiment has a moisture permeability of 500 g / m at a thickness of 100 μm, measured in accordance with JIS Z 0208:1976 after exposure to an environment of 85° C. and 85% RH for 24 hours. 2 It is preferable that the thickness is less than 400 g / m 2 More preferably, it is 350 g / m or less. 2 When the moisture permeability is low, the occurrence of dark spots due to moisture reaching the organic light emitting material layer can be more significantly suppressed.

[0129] The method of using the composition of the present embodiment is not particularly limited. The composition of the present embodiment can be suitably used as a sealant for an organic EL display element. Specifically, for example, the composition is applied to an object (for example, an organic EL display element) and the composition is cured on the object, thereby forming a sealant made of a cured body of the composition.

[0130] The composition may be cured into a predetermined shape (e.g., a film, a sheet, etc.) to form a sealant having a predetermined shape. In this case, for example, the sealant can be disposed on an organic EL display element to seal the organic EL display element.

[0131] The composition of the present embodiment has excellent surface flatness and linearity, and therefore, even when applied to an inkjet method, an organic film having a surface with few irregularities can be accurately formed in a predetermined area. For this reason, the composition of the present embodiment can be suitably used as a coating liquid for forming an organic film (preferably an organic film as a sealant for an organic EL display element) by an inkjet method.

[0132] Hereinafter, one aspect of an organic EL display device formed using the composition of the present embodiment as a sealant will be described with a top-emission organic EL display device as an example. Note that the organic EL display device to which the composition of the present embodiment is applied is not limited to the top-emission type, and may be a bottom-emission type organic EL display device in which light generated in the organic EL layer is irradiated from the substrate side.

[0133] A top-emission type organic EL display device includes an organic EL display element, a sealing layer that seals the organic EL display element, and a sealing substrate provided on the sealing layer.

[0134] An organic EL display element has a structure in which, for example, an anode, an organic EL layer including a light-emitting layer, and a cathode are laminated in this order on a substrate.

[0135] Examples of the substrate for the organic EL display element include a glass substrate, a silicon substrate, a plastic substrate, etc. Among these, a glass substrate and a plastic substrate are preferred, and a glass substrate is more preferred.

[0136] Examples of plastics used for the plastic substrate include polyimide, polyetherimide, polyethylene terephthalate, polyethylene naphthalate, polyoxadiazole, aromatic polyamide, polybenzimidazole, polybenzobisthiazole, polybenzoxazole, polythiazole, polyparaphenylene vinylene, polymethyl methacrylate, polystyrene, polycarbonate, polycycloolefin, polyacrylic, etc. Among these, in terms of low moisture permeability, low oxygen permeability, and excellent heat resistance, one or more of the group consisting of polyimide, polyetherimide, polyethylene terephthalate, polyethylene naphthalate, polyoxadiazole, aromatic polyamide, polybenzimidazole, polybenzobisthiazole, polybenzoxazole, polythiazole, and polyparaphenylene vinylene are preferred, and in terms of high transmittance of energy rays such as ultraviolet rays or visible light, one or more of the group consisting of polyimide, polyetherimide, polyethylene terephthalate, and polyethylene naphthalate are more preferred.

[0137] As the anode, a conductive metal oxide film or a semitransparent metal thin film having a relatively large work function (preferably one having a work function larger than 4.0 eV) is generally used. Examples of the material of the anode include metal oxides such as indium tin oxide (hereinafter referred to as ITO) and tin oxide, metals such as gold (Au), platinum (Pt), silver (Ag), copper (Cu), or alloys containing at least one of these, and organic transparent conductive films such as polyaniline or its derivatives, polythiophene or its derivatives. If necessary, the anode can be formed in a layer structure of two or more layers. The thickness of the anode can be appropriately selected taking into consideration the electrical conductivity (and the light transmittance in the case of a bottom emission type). The thickness of the anode is preferably 10 nm to 10 μm, more preferably 20 nm to 1 μm, and most preferably 50 nm to 500 nm. That is, the thickness of the anode may be, for example, 10 nm to 10 μm, 10 nm to 1 μm, 10 nm to 500 nm, 20 nm to 10 μm, 20 nm to 1 μm, 20 nm to 500 nm, 50 nm to 10 μm, 50 nm to 1 μm, or 50 nm to 500 nm. Methods for producing the anode include vacuum deposition, sputtering, ion plating, and plating. In the case of a top emission type, a reflective film for reflecting light irradiated to the substrate side may be provided under the anode.

[0138] The organic EL layer includes at least a light-emitting layer made of an organic material. The light-emitting layer contains a light-emitting material. Examples of the light-emitting material include organic materials (low molecular weight compounds or polymer compounds) that emit fluorescence or phosphorescence. The light-emitting layer may further contain a dopant material. Examples of the organic material include dye-based materials, metal complex-based materials, polymer materials, and the like. The dopant material is doped into the organic material for the purpose of improving the light-emitting efficiency of the organic material or changing the emission wavelength. The thickness of the light-emitting layer made of these organic materials and the dopant that is doped as necessary is usually 2 to 200 nm.

[0139] Examples of dye-based materials include cyclopentamine derivatives, tetraphenylbutadiene derivative compounds, triphenylamine derivatives, oxadiazole derivatives, pyrazoloquinoline derivatives, distyrylbenzene derivatives, distyrylarylene derivatives, pyrrole derivatives, thiophene ring compounds, pyridine ring compounds, perinone derivatives, perylene derivatives, oligothiophene derivatives, triphimanylamine derivatives, oxadiazole dimers, and pyrazoline dimers.

[0140] Examples of metal complex-based materials include metal complexes having emission from triplet excited states, such as iridium complexes and platinum complexes, aluminum quinolinol complexes, benzoquinolinol beryllium complexes, benzoxazolyl zinc complexes, benzothiazole zinc complexes, azomethyl zinc complexes, porphyrin zinc complexes, and europium complexes. Examples of metal complexes include metal complexes having rare earth metals such as terbium (Tb), europium (Eu), and dysprosium (Dy), aluminum (Al), zinc (Zn), and beryllium (Be), as central metals, and having oxadiazole, thiadiazole, phenylpyridine, phenylbenzimidazole, and quinoline structures, as ligands. Among these, metal complexes having aluminum (Al) as central metals and having quinoline structures, as ligands, are preferred. Among metal complexes having aluminum (Al) as central metals and having quinoline structures, as ligands, tris(8-hydroxyquinolinato)aluminum is preferred.

[0141] Examples of the polymeric material include polyparaphenylenevinylene derivatives, polythiophene derivatives, polyparaphenylene derivatives, polysilane derivatives, polyacetylene derivatives, polyfluorene derivatives, polyvinylcarbazole derivatives, and polymerized products of the above-mentioned colorants and metal complex-based luminescent materials.

[0142] Among the above-mentioned light-emitting materials, materials that emit blue light include distyrylarylene derivatives, oxadiazole derivatives, polyvinylcarbazole derivatives, polyparaphenylene derivatives, polyfluorene derivatives, and polymers thereof. Among these, polymer materials are preferred. Among the polymer materials, at least one selected from the group consisting of polyvinylcarbazole derivatives, polyparaphenylene derivatives, and polyfluorene derivatives is preferred.

[0143] Examples of materials that emit green light include quinacridone derivatives, coumarin derivatives, polyparaphenylenevinylene derivatives, polyfluorene derivatives, and polymers thereof. Among these, polymer materials are preferred. Among polymer materials, at least one selected from the group consisting of polyparaphenylenevinylene derivatives and polyfluorene derivatives is preferred.

[0144] Examples of materials that emit red light include coumarin derivatives, thiophene ring compounds, polyparaphenylenevinylene derivatives, polythiophene derivatives, polyfluorene derivatives, and polymers thereof. Among these, polymer materials are preferred. Among polymer materials, at least one selected from the group consisting of polyparaphenylenevinylene derivatives, polythiophene derivatives, and polyfluorene derivatives is preferred.

[0145] Examples of the dopant material include perylene derivatives, coumarin derivatives, rubrene derivatives, quinacridone derivatives, squarium derivatives, porphyrin derivatives, styryl dyes, tetracene derivatives, pyrazolone derivatives, decacyclene, and phenoxazone.

[0146] In addition to the light-emitting layer, the organic EL layer may appropriately include a layer provided between the light-emitting layer and the anode, and a layer provided between the light-emitting layer and the cathode. First, the layer provided between the light-emitting layer and the anode may include a hole injection layer that improves the efficiency of hole injection from the anode, and a hole transport layer that transports holes injected from the anode or the hole injection layer to the light-emitting layer. The layer provided between the light-emitting layer and the cathode may include an electron injection layer that improves the efficiency of electron injection from the cathode, and an electron transport layer that transports electrons injected from the cathode or the electron injection layer to the light-emitting layer.

[0147] Examples of materials for forming the hole injection layer include phenylamines such as 4',4''-tris{2-naphthyl(phenyl)amino}triphenylamine, starburst amines, phthalocyanines, oxides such as vanadium oxide, molybdenum oxide, ruthenium oxide, and aluminum oxide, amorphous carbon, polyaniline, and polythiophene derivatives.

[0148] Examples of materials constituting the hole transport layer include polyvinylcarbazole or a derivative thereof, polysilane or a derivative thereof, a polysiloxane derivative having an aromatic amine in the side chain or the main chain, a pyrazoline derivative, an arylamine derivative, a stilbene derivative, a triphenyldiamine derivative, a benzidine derivative, polyaniline or a derivative thereof, polythiophene or a derivative thereof, a polyarylamine or a derivative thereof, polypyrrole or a derivative thereof, poly(p-phenylenevinylene) or a derivative thereof, and poly(2,5-thienylenevinylene) or a derivative thereof.

[0149] When the hole injection layer or the hole transport layer has a function of blocking the transport of electrons, it is sometimes called an electron blocking layer.

[0150] Examples of materials constituting the electron transport layer include oxadiazole derivatives, anthraquinodimethane or its derivatives, benzoquinone or its derivatives, naphthoquinone or its derivatives, anthraquinone or its derivatives, tetracyanoanthraquinodimethane or its derivatives, fluorenone derivatives, diphenyldicyanoethylene or its derivatives, diphenoquinone derivatives, 8-hydroxyquinoline or its derivatives, polyquinoline or its derivatives, polyquinoxaline or its derivatives, polyfluorene or its derivatives, and the like. Examples of derivatives include metal complexes, and the like. Among these, 8-hydroxyquinoline or its derivatives are preferred. Among 8-hydroxyquinoline or its derivatives, tris(8-hydroxyquinolinato)aluminum is preferred because it can also be used as an organic material that emits fluorescence or phosphorescence and is contained in the light-emitting layer.

[0151] The electron injection layer may be, depending on the type of the light-emitting layer, a single-layer structure of a calcium (Ca) layer, a single-layer structure of a layer formed of at least one of the group consisting of metals in Groups IA and IIA of the periodic table and having a work function of 1.5 to 3.0 eV, and oxides, halides, and carbonates of the metals, or a laminate structure of a layer formed of at least one of the group consisting of metals in Groups IA and IIA of the periodic table and having a work function of 1.5 to 3.0 eV, and oxides, halides, and carbonates of the metals, and a Ca layer. Examples of metals in Group IA of the periodic table and having a work function of 1.5 to 3.0 eV, or oxides, halides, and carbonates of the metals, include lithium (Li), lithium fluoride, sodium oxide, lithium oxide, and lithium carbonate. Examples of metals in Group IIA of the periodic table having a work function of 1.5 to 3.0 eV or oxides, halides, and carbonates thereof include strontium (Sr), magnesium oxide, magnesium fluoride, strontium fluoride, barium fluoride, strontium oxide, and magnesium carbonate.

[0152] When the electron transport layer or the electron injection layer has a function of blocking the transport of holes, the electron transport layer or the electron injection layer is sometimes called a hole blocking layer.

[0153] The cathode is preferably a transparent or semi-transparent material that has a relatively small work function (preferably one having a work function of less than 4.0 eV) and that allows easy injection of electrons into the light-emitting layer. Examples of the cathode material include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), scandium (Sc), vanadium (V), zinc (Zn), yttrium (Y), indium (In), cerium (Ce), samarium (Sm), europium (Eu), terbium (Tb), and the like. Examples of the metal include metals such as copper (Au), silver (Ag), platinum (Pt), copper (Cu), chromium (Cr), manganese (Mn), titanium (Ti), cobalt (Co), nickel (Ni), tungsten (W), and tin (Sn), as well as graphite or graphite intercalation compounds, and metal oxides such as ITO and tin oxide.

[0154] The cathode may have a laminated structure of two or more layers. Examples of the laminated structure of two or more layers include a laminated structure of the above-mentioned metals, metal oxides, fluorides, and alloys thereof with metals such as Al, Ag, and Cr. The thickness of the cathode can be appropriately selected in consideration of electrical conductivity and durability. The thickness of the cathode is preferably 10 nm to 10 μm, more preferably 15 nm to 1 μm, and most preferably 20 nm to 500 nm. That is, the thickness of the cathode may be, for example, 10 nm to 10 μm, 10 nm to 1 μm, 10 nm to 500 nm, 15 nm to 10 μm, 15 nm to 1 μm, 15 nm to 500 nm, 20 nm to 10 μm, 20 nm to 1 μm, or 20 nm to 500 nm. Examples of the method for producing the cathode include a vacuum deposition method, a sputtering method, and a lamination method in which a metal thin film is thermocompressed.

[0155] The layers provided between the light-emitting layer and the anode, and between the light-emitting layer and the cathode can be appropriately selected according to the performance required for the organic EL display device to be manufactured. For example, the structure of the organic EL display element used in this embodiment can have any of the layer configurations (i) to (xv) below. (i) Anode / hole transport layer / light emitting layer / cathode (ii) anode / light-emitting layer / electron transport layer / cathode (iii) anode / hole transport layer / light emitting layer / electron transport layer / cathode (iv) Anode / hole injection layer / light emitting layer / cathode (v) Anode / light-emitting layer / electron injection layer / cathode (vi) Anode / hole injection layer / light emitting layer / electron injection layer / cathode (vii) Anode / hole injection layer / hole transport layer / light emitting layer / cathode (viii) Anode / hole transport layer / light emitting layer / electron injection layer / cathode (ix) Anode / hole injection layer / hole transport layer / light emitting layer / electron injection layer / cathode (x) Anode / hole injection layer / light emitting layer / electron transport layer / cathode (xi) Anode / light-emitting layer / electron transport layer / electron injection layer / cathode (xii) Anode / hole injection layer / light emitting layer / electron transport layer / electron injection layer / cathode (xiii) Anode / hole injection layer / hole transport layer / light emitting layer / electron transport layer / cathode (xiv) Anode / hole transport layer / light emitting layer / electron transport layer / electron injection layer / cathode (xv) Anode / hole injection layer / hole transport layer / light emitting layer / electron transport layer / electron injection layer / cathode (Here, " / " indicates that each layer is stacked adjacently. The same applies below.)

[0156] The sealing layer is provided to seal the organic EL display element with a layer having high barrier properties against gases such as water vapor and oxygen in order to prevent the organic EL display element from coming into contact with the element. This sealing layer is formed by alternately forming inorganic films and organic films from below. The inorganic / organic laminate may be formed two or more times.

[0157] The inorganic film of the inorganic / organic laminate is a film provided to prevent the organic EL display element from being exposed to gases such as water vapor and oxygen present in the environment in which the organic EL display device is placed. The inorganic film of the inorganic / organic laminate is preferably a continuous dense film with few defects such as pinholes. Examples of the inorganic film include single films such as SiN film, SiO film, SiON film, Al2O3 film, and AlN film, and laminated films thereof.

[0158] The organic film of the inorganic / organic laminate is provided to cover defects such as pinholes formed on the inorganic film and to provide flatness to the surface. The organic film is formed in an area narrower than the area where the inorganic film is formed. This is because if the organic film is formed to be the same as or wider than the area where the inorganic film is formed, the organic film will deteriorate in the area where it is exposed. However, the top organic film formed on the top layer of the entire sealing layer is formed in approximately the same area as the area where the inorganic film is formed. And, it is formed so that the upper surface of the sealing layer is flattened. The organic film may be a film formed using the composition of the present embodiment described above (i.e., a film including a cured body of the composition).

[0159] As described above, the composition of the present embodiment is suitable for inkjet coating, and has excellent ejectability by inkjet and flatness after inkjet coating. By using a coating method by the inkjet method, an organic film can be formed quickly and uniformly.

[0160] The sealing layer is preferably 1 to 5 sets, counting the inorganic / organic laminate as one set. When the inorganic / organic laminate is 6 sets or more, the sealing effect for the organic EL display element is almost the same as when it is 5 sets. The thickness of the inorganic film of the inorganic / organic laminate is preferably 50 nm to 1 μm. The thickness of the organic film of the inorganic / organic laminate is preferably 1 to 15 μm, more preferably 3 to 10 μm. When the thickness of the organic film is 1 μm or more, particles generated during element formation can be completely covered, and the organic film can be applied with good flatness. When the thickness of the organic film is 15 μm or less, moisture does not penetrate from the side of the organic film, improving the reliability of the organic EL display element. The thickness of the organic film of the inorganic / organic laminate may be, for example, 1 to 15 μm, 1 to 10 μm, 3 to 15 μm, or 3 to 10 μm.

[0161] The sealing substrate is formed so as to cover the entire upper surface of the uppermost organic film of the sealing layer in close contact with the substrate. Examples of the sealing substrate include the above-mentioned substrates. Among these, a substrate transparent to visible light is preferred. Among substrates (transparent sealing substrates) transparent to visible light, one or more selected from the group consisting of glass substrates and plastic substrates are preferred, and a glass substrate is more preferred.

[0162] The thickness of the transparent sealing substrate is preferably 1 μm to 1 mm, more preferably 10 μm to 800 μm, and most preferably 50 μm to 300 μm. By providing the transparent sealing substrate on the sealing layer, deterioration that progresses when the surface of the uppermost organic film is exposed to gas can be suppressed, and the barrier property of the organic EL display device can be improved. The thickness of the transparent sealing substrate may be, for example, 1 μm to 1 mm, 1 μm to 800 μm, 1 μm to 300 μm, 10 μm to 1 mm, 10 μm to 800 μm, 10 μm to 300 μm, 50 μm to 1 mm, 50 μm to 800 μm, or 50 μm to 300 μm.

[0163] Next, a method for manufacturing an organic EL display device having such a configuration will be described. First, an anode patterned into a predetermined shape, an organic EL layer including a light-emitting layer, and a cathode are formed in this order on a first substrate by a conventionally known method to form an organic EL display element. For example, when the organic EL display device is used as a dot matrix display device, banks are formed to separate the light-emitting region into a matrix shape, and the organic EL layer including the light-emitting layer is formed in the region surrounded by the banks.

[0164] Next, a first inorganic film having a predetermined thickness is formed on the substrate on which the organic EL display element is formed by a film forming method such as a PVD (Physical Vapor Deposition) method such as a sputtering method or a CVD method such as a plasma CVD (Chemical Vapor Deposition) method. Then, the composition (sealant) of the present embodiment is attached to the first inorganic film by using a coating film forming method such as a solution coating method or a spray coating method, a flash deposition method, an inkjet method, or the like. Among these, the inkjet method is preferred in terms of productivity. Then, the sealant is cured by irradiation with energy rays such as ultraviolet rays and visible light, and a first organic film is formed. By the above steps, one set of inorganic / organic laminates is formed. The curing rate of the sealant is not particularly limited as long as the effect of the present embodiment is achieved, but can be, for example, 90% or more, preferably 95% or more, as a value obtained according to a measurement method described later.

[0165] The above-described process for forming an inorganic / organic laminate is repeated a predetermined number of times. However, for the last set, i.e., the topmost inorganic / organic laminate, a sealant may be applied to the top surface of the inorganic film by a coating method, a flash deposition method, an inkjet method, or the like so as to flatten the top surface.

[0166] Next, a transparent sealing substrate is bonded to the surface of the substrate to which the sealant is attached. When bonding, alignment is performed. Thereafter, energy rays are irradiated from the transparent sealing substrate side to harden the sealant of this embodiment present between the uppermost inorganic film and the transparent sealing substrate. This hardens the sealant to form the uppermost organic film and bond the uppermost organic film to the transparent sealing substrate. This completes the method for manufacturing an organic EL display device.

[0167] After the sealant is applied onto the inorganic film, it may be partially irradiated with energy rays to polymerize it. In this way, it is possible to prevent the shape of the top organic film from being distorted when the transparent sealing substrate is placed. The thicknesses of the inorganic film and the organic film may be the same for each inorganic / organic laminate, or may be different for each inorganic / organic laminate.

[0168] In this embodiment, the organic EL display device can be used as a surface light source, a segment display device, or a dot matrix display device.

[0169] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES

[0170] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0171] Details of the components used in the examples and comparative examples are as follows. The viscosity of the monomer components is a value measured by an E-type viscometer at 25°C. The surface tension of the monomer components is a value measured by a pendant drop method at 23°C. <Fluorine-containing monomer> "13F" Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat 13F" Compound name: 3,3,4,4,5,5,6,6,7,7,8,8,8-Tridecafluorooctyl acrylate Viscosity: 4mPa·s Surface tension: 12mN / m LINC-162A Kyoeisha Chemical Co., Ltd., product name "LINC-162A" Compound name: 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-Hexadecafluoro-1,10-decanediacrylate Viscosity: 32mPa·s Surface tension: 17mN / m

[0172] <Monomer (B)> "A-LEN-10" Product name: "NK Ester A-LEN-10" manufactured by Shin-Nakamura Chemical Co., Ltd. Compound name: Ethoxylated o-phenylphenol acrylate Viscosity: 150mPa·s Surface tension: 35mN / m "DCPA" Product name: "NK Ester A-DCP" manufactured by Shin-Nakamura Chemical Co., Ltd. Compound name: Tricyclodecane dimethanol diacrylate Viscosity: 120mPa·s Surface tension: 33mN / m "BPE200" Product name: "NK Ester BPE-200" manufactured by Shin-Nakamura Chemical Co., Ltd. Compound name: Ethoxylated bisphenol A dimethacrylate Viscosity: 600mPa·s Surface tension: 37mN / m SR262 Manufactured by Arkema, product name "SR262" Compound name: 1,12-dodecanediol dimethacrylate Viscosity: 12mPa·s Surface tension: 26mN / m UG4010 Manufactured by Toagosei Co., Ltd., product name "Alphon" Compound name: Acrylic polymer Viscosity: 3700mPa·s Surface tension: 45mN / m

[0173] <Photopolymerization initiator> "TPO" Manufactured by iGM Resins, product name "Omnirad TPO" Compound name:Diphenyl-2,4,6-trimethylbenzoylphosphine oxide

[0174] Example 1 A composition was prepared by mixing 1 part by mass of "LINC-162A", 5 parts by mass of "A-LEN-10", 18 parts by mass of "DCPA", 76 parts by mass of "SR262", and 3.5 parts by mass of "TPO". That is, the proportion of fluorine-containing monomer in the monomer components was 1 mass%, the proportion of high-viscosity monomer was 23 mass%, and the proportion of bifunctional monomer was 95 mass%. The viscosity of the obtained composition (measured by an E-type viscometer at 25°C) was 16 mPa·s, and the surface tension was 26 mN / m.

[0175] Example 2 A composition was prepared by mixing 1 part by mass of "LINC-162A", 5 parts by mass of "A-LEN-10", 15 parts by mass of "DCPA", 3 parts by mass of "BPE200", 76 parts by mass of "SR262", and 3.5 parts by mass of "TPO". That is, the proportion of fluorine-containing monomer in the monomer components was 1% by mass, the proportion of high-viscosity monomer was 23% by mass, and the proportion of bifunctional monomer was 95% by mass. The viscosity of the obtained composition (measured by an E-type viscometer at 25°C) was 17 mPa·s, and the surface tension was 27 mN / m.

[0176] Example 3 A composition was prepared by mixing 1 part by mass of "13F", 5 parts by mass of "A-LEN-10", 18 parts by mass of "DCPA", 76 parts by mass of "SR262", and 3.5 parts by mass of "TPO". That is, the proportion of fluorine-containing monomer in the monomer components was 1% by mass, the proportion of high-viscosity monomer was 23% by mass, and the proportion of bifunctional monomer was 94% by mass. The viscosity of the obtained composition (measured by an E-type viscometer at 25°C) was 16 mPa·s, and the surface tension was 25 mN / m.

[0177] Example 4 A composition was prepared by mixing 0.01 parts by mass of "LINC-162A", 5 parts by mass of "A-LEN-10", 18 parts by mass of "DCPA", 76.99 parts by mass of "SR262", and 3.5 parts by mass of "TPO". That is, the proportion of fluorine-containing monomer in the monomer components was 0.01% by mass, the proportion of high-viscosity monomer was 23% by mass, and the proportion of bifunctional monomer was 95% by mass. The viscosity of the obtained composition (measured by an E-type viscometer at 25°C) was 16 mPa·s, and the surface tension was 27 mN / m.

[0178] Example 5 A composition was prepared by mixing 5 parts by mass of "LINC-162A", 15 parts by mass of "A-LEN-10", 15 parts by mass of "DCPA", 65 parts by mass of "SR262", and 5 parts by mass of "TPO". That is, the ratio of the fluorine-containing monomer in the monomer components was 5% by mass, the ratio of the high-viscosity monomer was 30% by mass, and the ratio of the bifunctional monomer was 85% by mass. The viscosity of the obtained composition (measured by an E-type viscometer at 25°C) was 14 mPa·s, and the surface tension was 24 mN / m.

[0179] Comparative Example 1 A composition was prepared by mixing 5 parts by mass of "A-LEN-10", 18 parts by mass of "DCPA", 77 parts by mass of "SR262", and 3.5 parts by mass of "TPO". That is, in the monomer components, the proportion of fluorine-containing monomer was 0% by mass, the proportion of high-viscosity monomer was 23% by mass, and the proportion of bifunctional monomer was 95% by mass. The viscosity of the obtained composition (measured by an E-type viscometer at 25°C) was 16 mPa s, and the surface tension was 27 mN / m.

[0180] Comparative Example 2 1 part by mass of "LINC-162A", 5 parts by mass of "UG4010", 18 parts by mass of "DCPA", 76 parts by mass of "SR262", and 3.5 parts by mass of "TPO" were mixed to prepare a composition. That is, in the monomer component, the proportion of the fluorine-containing monomer was 1% by mass, the proportion of the high-viscosity monomer was 18% by mass (23% by mass including "UG4010" that does not satisfy formula (vi)), and the proportion of the bifunctional monomer was 95% by mass. The viscosity of the obtained composition (the value measured by an E-type viscometer at 25°C) was 20 mPa·s, and the surface tension was 28 mN / m.

[0181] (Comparative Example 3) 95 parts by mass of "13F", 5 parts by mass of "BPE200", and 3.5 parts by mass of "TPO" were mixed to prepare a composition. That is, in the monomer component, the proportion of the fluorine-containing monomer was 95% by mass, the proportion of the high-viscosity monomer was 5% by mass, and the proportion of the bifunctional monomer was 5% by mass. The viscosity of the obtained composition (the value measured by an E-type viscometer at 25°C) was 6 mPa·s, and the surface tension was 15 mN / m.

[0182] The compositions obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were evaluated by the following method. The results are shown in Table 1.

[0183] <E-type Viscosity> The viscosity of the composition was measured using an E-type viscometer (cone-and-plate type: cone angle 1°34′, radius of cone rotor 24 mm) under the conditions of a temperature of 25°C and a rotation speed of 100 rpm. <Surface Tension> The surface tension of the composition was measured by the pendant drop method using a contact angle meter (DM500 manufactured by Kyowa Interface Science Co., Ltd.) in an atmosphere at 23°C.

[0184] <Evaluation of Surface Flatness and Edge Flatness> On a substrate (alkali-free glass (Corning Eagle XG)) of 70 mm x 70 mm x 0.7 mmt, 25 μm x 25 μm x 3 μmt recesses were prepared by etching with 10 μm intervals in the front, back, left and right directions. Next, a 200 nm SiN film was formed on the substrate with the recesses by plasma CVD. Next, the composition was pattern-coated to 15 mm x 15 mm x 8 μmt using an inkjet discharge device (MID500B, solvent-based head "MID head" manufactured by Musashi Engineering Co., Ltd.). Note that the substrate was washed with acetone and isopropanol before the pattern coating, and then washed for 5 minutes using a UV ozone cleaning device UV-208 manufactured by Technovision Co., Ltd. After applying the pattern, the sample was left in a nitrogen atmosphere for 4 minutes at a temperature of 23°C and a relative humidity of 50%, and then exposed to an LED lamp (HOYA UV-LED LIGHT SOURCE H-4MLH200-V1) emitting light with a wavelength of 395 nm under a nitrogen atmosphere with an integrated light intensity of 1,500 mJ / cm 2 The composition was photocured under the conditions below. Next, the thickness of the cured film was measured in a direction perpendicular to the direction of head movement using a stylus-type shape measuring device (DektakXT manufactured by BRUKER). The difference between the maximum thickness and the minimum thickness within a surface excluding 2 mm from the end of the cured film was used as the evaluation result of surface flatness. In addition, the difference between the maximum thickness and the minimum thickness within a range of 2 mm from one end of the cured film was used as the evaluation result of edge flatness.

[0185] <Evaluation of moisture permeability> A 0.1 mm thick sheet-like cured product was produced under the above photocuring conditions. In accordance with JIS Z0208:1976 "Test method for moisture permeability of moisture-proof packaging materials (cup method)", calcium chloride (anhydrous) was used as a moisture absorbent, and the cured product was exposed to conditions of 85°C and 85% relative humidity for 24 hours, and the moisture permeability of the cured product at a thickness of 100 μm was measured.

[0186] [Table 1]

[0187] As shown in Table 1, the compositions of the examples achieved both excellent edge flatness and surface flatness. In addition, the compositions of the examples formed cured products with sufficiently low moisture permeability, and it was confirmed that they are useful as encapsulants for organic EL display elements.

[0188] Furthermore, as shown in Table 1, Comparative Example 1, which did not contain a fluorine-containing monomer, showed poor surface flatness. Comparative Example 2, which contained 5 mass% of "UG4010" with a viscosity of 3700 mPa s, showed poor edge flatness and surface flatness. Comparative Example 3, which contained 5 mass% of "BPE200" with a surface tension of 37 mN / m, showed poor edge flatness and moisture permeability.

Claims

1. A monomer component, A photopolymerization initiator; Including, 97% by mass or more of the monomer components are monomers that satisfy the following formulas (i) and (ii): 0.1 to 10 mass % of the monomer component is a fluorine-containing monomer which satisfies the following formula (iii) and has a fluorine atom and a carbon-carbon unsaturated double bond, 5 to 23 mass % of the monomer component is a high-viscosity monomer that satisfies the following formula (vi) and has a viscosity of 50 mPa s or more at 25° C., The composition, wherein 70 to 98 mass % of the monomer component is a polyfunctional monomer having two or more carbon-carbon unsaturated double bonds. |c C -c A |<20mN / m …(i) [In the formula, γ C represents the surface tension of the composition (mN / m), and γ A indicates the surface tension of the monomer (mN / m). |η A -η C | < 3000 mPa·s …(ii) [In the formula, η C represents the viscosity (mPa·s) of the composition at 25° C., and η A indicates the viscosity (mPa·s) of the monomer at 25° C.] 1-Pa・s≦|η A1 -η C |≦30mPa·s …(iiiii) [In the formula, η C represents the viscosity (mPa·s) of the composition at 25° C., and η A1 indicates the viscosity (mPa·s) of the fluorine-containing monomer at 25° C.] 50Ma・b≦|η A2 -or C |<3000mPa・s …(vv) [In the formula, η C represents the viscosity (mPa·s) of the composition at 25° C., and η A2 indicates the viscosity (mPa·s) of the high viscosity monomer at 25° C.]

2. The composition according to claim 1, wherein the fluorine-containing monomer satisfies the following formula (iii-a): 5Ma・b≦|η A1 -or C |≦20mPa・s …(ym-a)

3. The composition according to claim 1 or 2, wherein the high viscosity monomer satisfies the following formula (iv-a): 70mPa・s≦|h A2 -or C |≦1000mPa・s …(gv-a)

4. The surface tension γ of the composition C The composition according to any one of claims 1 to 3, wherein the elastic modulus is 10 mN / m or more and 50 mN / m or less.

5. The viscosity η of the composition at 25°C C The composition according to any one of claims 1 to 4, wherein the viscosity is 3 mPa·s or more and 50 mPa·s or less.

6. The composition according to any one of claims 1 to 5, which is a sealant for an organic electroluminescence display device.

7. A cured product obtained by curing the composition according to any one of claims 1 to 6.

8. A sealing material for an organic electroluminescence display device, comprising the cured product according to claim 7 .

9. The laminate includes an inorganic film and an organic film, The organic film comprises the cured product according to claim 7. A sealing material for an organic electroluminescence display element.

10. An organic electroluminescence display element; The sealing material for an organic electroluminescence display element according to claim 8 or 9, An organic electroluminescent display device comprising:

Citation Information

Patent Citations

  • Organic electroluminescence display element and its manufacturing method

    JP2001307873A

  • Organic el device and its manufacturing method

    JP2009037812A

  • Photocurable composition and patterned body manufactured by using the composition

    US20180298182A1

  • Sealing agent for organic electroluminescent display elements

    WO2019082996A1

  • Fluorinated monomer, fluorinated polymer, curable composition, and production method for pattern

    WO2019189556A1